Material Development for Arabic Writing Skills Based on International Standards l Tathwir al-Mawad al-Dirasiyyah li Maharah al-Kitabah fi Dhau’i al-Ma‘ayir al-‘Alamiyyah - Nuraini, Nuraini; Asrori, Imam; Hasanah, Mamluatul (Universitas Islam Negeri Raden Intan Lampung, 2022)
The main source of language teaching is teaching materials. The important aspects in developing the language curriculum depend on these materials and their use in the language. Preparing materials must be adapted to the competencies and needs of the students. This study aimed to develop the teaching materials of arabic writing skills for the beginners levels based on intenational standards. The documents were the arabic writing materials for the beginers levels. Meanwhile, interview was conducted with the directur and teacher of Arabic language and the students of Islamic Study Programs, with an expert in the curriculum of arabic language and the material of arabic writing skills. The finding of this study were the material for writing skill of arabic language for the beginners levels which based on internationals standards. The materials teaching of the beginers levels were suitable with the levels of arabic learners which developed by the American Council on the teaching of foreign language (ACTFL). It consist the levels of arabic learning, thus are Novice, Intermediate, Advance and Superiors levels. The results of this study showed that the writing skills for the beginers levels must be started with the writtng diction, simple sentences, and short paragraphs. The results proved that materials teaching of arabic writing skills for the beginers levels is effective for Improving the students competency in arabic writing. Thus, this research suggest the students needs to be involved to solve the problem related to the Arabic language skills of students from diverse educational backgrounds.